On Delegation under Relational Contracts - Oliver Gürtler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In this paper, a principal's decision between delegating two tasks or handling one of the two tasks herself is analyzed. We assume that the principal uses both, formal contracts and informal agreements sustained by the value of future relationships (relational contracts) as incentive device. It is found that the principal is less likely to delegate both tasks in a dynamic setting than in a static one (where formal contracts are the only feasible incentive device), as handling one task herself enables a much wider use of relational contracts.
urn:nbn:de:bvb:19-epub-13438-2
Keywords: D82; J33; L23; M52; M54; 330; Job design; relational contracts; formal contracts; delegation